Recurrent ileo-ileal intussusception caused by inflammatory fibroid polyp: a rare case report - ERGENÇ, MUHAMMER (My University, 2023)
An inflammatory fibroid polyp is a rare benign lesion of the gastrointestinal tract, which can cause obstruction or intussusception when it reaches a large diameter. We present a case of a 46-year-old female admitted to our clinic with recurrent ileus attacks. We performed segmental resection of the small bowel due to a 3-cm pedunculated polypoid lesion located in the terminal ileum that caused ileo-ileal intussusception and whose pathology was reported as an inflammatory fibroid polyp. In adults presenting with ileus, the possibility of intussusception should be kept in mind.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Genel Cerrahi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; General Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; Cerrahi; Surgery